Rufous Hornero ( Furnarius rufus , Furnariidae) anointing with a millipede (Diplopoda, Spirobolidae) in southernmost Brazil - Amanda Perin Marcon; João Vitor Perin Andriola (Journal of Field Ornithology, 2023)
Anointing is a rarely observed and poorly understood behavior performed by more than 200 species of birds in which individuals actively or passively rub ants or other animals/objects onto their feathers, presumably to remove ectoparasites, heal infections, or soothe irritated skin during molting. Millipedes can be used for anointing, probably because of their secretions, which are filled with chemical substances that may contribute to removing ectoparasites, treating dermal diseases, and enhancing olfactory communication. Only three records of millipede-anointing for two species of Neotropical birds are known; our observation identifies a third species. We observed and described a Rufous Hornero ( Furnarius rufus ) anointing with a millipede for 100 sec, as it mainly focused on its cloaca while pecking and hitting the millipede on the ground, which was possibly a tactic to obtain more fluids. The higher amount of time spent anointing the cloaca region could be linked to the elimination of bacteria or infections, or to reduce dermal irritation, possibly making it more attractive to the opposite sex, as it would seem healthy and clean. Another hypothesis is that the bird was self-stimulating, although most authors do not support this interpretation. Anointing is still not well understood by science, and more research as well as detailed observations are encouraged.